Depreciación de propiedad, planta y equipo según las NIIF. - Martinez Rios, Jessica Alexandra (My University, 2019)
The objective of this research work is to calculate the annual depreciation of a computer equipment with a useful life of 4 years, according to the International Financial Reporting Standards (IFRS) 16 Leases, where it stipulates the depreciation methods of Property, Plant and Equipment in IAS 16, this standard has the accounting treatment of these fixed assets. Through these methods of depreciation through the application of the same we will know clearly and accurately the depreciation of the asset that has suffered during the life cycle in the operations performed in the company and the depreciation value. It is mandatory that all companies keep in their accounting records the adoption of IFRS because it is a very effective source of carrying their financial statements and really know what is happening in the company and its environment in terms of property, plant and team. For the investigation of this work has been taken as a guide scientific articles on the subject, which is considered the best source of reliable research for the interpretation of the exercise.
El presente trabajo de investigación tiene como objetivo el cálculo de la depreciación anual de un equipo de computación con una vida útil de 4 años, según las Normas Internacionales de Información Financiera (NIIF) 16 Arrendamientos, donde estipula los métodos de depreciación de Propiedad, Planta y Equipo en la NIC 16, esta norma tiene el tratamiento contable de estos activos fijos. Por medio de estos métodos de depreciación mediante la aplicación de la misma vamos a conocer de forma clara y precisa la depreciación del activo que ha sufrido durante el ciclo de vida útil en las operaciones ejercidas en la empresa y el valor de depreciación. Es de carácter obligatorio que todas las empresas lleven en sus registros contables la adopción de las NIIF porque es una fuente muy eficaz de llevar sus estados financieros y saber realmente lo que está sucediendo en la empresa y su entorno en cuanto a los bienes Propiedad, planta y Equipo. Para la investigación de este trabajo se ha tomado como guía artículos científicos referidos al tema, donde se considera la mejor fuente de investigación fiable para la interpretación del ejercicio planteado.
Keywords: CONTABILIDAD; NIIF; DEPRECIACIÓN; VALOR; ACTIVO FIJO